KAJIAN LABORATORIUM CAMPURAN ASBUTON DENGAN GRADASI SUPERPAVE TERHADAP FLEXURE FATIGUE TEST - Adwang, Jimmy
Natural Asphalt in Indonesia which are located in Buton island, has a huge deposit and has not been fully utilized actually for asphaltic concrete mixtures. A wider utilization of this material should be attempted in utilized construction road and maintenance program. he objective of this research is to investigate the influence of using Asbuton in Asphaltic concrete mixtures on the fatigue performances by using a fatigue test machine DARI'EC. The test has been carried out by applying a stress-controlled and sinusoidal loading pattern, three point loading method. The test was conducted at a room temperature. Gradation used is Superpave gradation based on Asphalt Institute (1996) with a maximum size of aggregate is 19 mm. he result of test on Superpave gradation with asbuton as fine aggregate and filler to fatigue performance indicated that asbuton can improve its fatigue performance of asphaltic concrete mixtures, i.e., highest fatigue life (238,121 cycles), highest effectiveness factor (521.44), highest initial stiffness (186.94 Mpa) and lowest rate of crack propagation (5,2906.52 cycles/mm) he result of test on Superpave gradation with asbuton as filler to fatigue performance showed that asbuton can improve a fatigue performance of concrete mixture also, i.e., fatigue life of 11,250 cycles, effectiveness factor of 6.76, give initial stiffness of 90.11 Mpa and rate of crack propagation of 485.50 cycles/mm. The result of test on Superpaves gradation with stone-ash on fatigue performance give lowest fatigue life (1,557 cycles), lowest effectiveness factor 1.00, lowest initial stiffness (49.76 Mpa) and highest rate of crack propagation (60.64 cycles/mm). The study concludes that Superpave gradation with asbuton as fine aggregate and filler is competent and can be use to change fine aggregate from crushed stone dan filler from stone ash in concrete mixtures. Key words : Asbuton, Superpave Gradation, Fatigue Test (Flexural Fatigue Test)